FORMATION OF PEDAGOGICAL SKILL OF THE FUTURE TEACHER USING VIDEO CONTENTS - Xamidjan Matyakubov (International Journal of Advanced Science and Technology, 2020)
The present article is dedicated to the process of formation of pedagogical skill of future teacher of the German language through video contents. The author of the article discusses the opinions of numerous scientists on the topic and gives her opinion concerning them. She also discusses the definitions given to different terms related to the topic. The peculiarities of using video contents in the lessons of the German language are discussed in the article.